Research on the mechanism of science-education-industry integration for cultivating innovative talents - Zhang, Lihong; Qu, Chengle (Global Journal of Social Sciences Studies, 2025)
The integration of science, education, and industry has become a prevailing philosophy in higher education. This educational philosophy expands the talent cultivation domain of universities and aligns more closely with the growth patterns of innovative talents, making it an inevitable choice for cultivating high-level innovative talents in China. This study aims to explore the internal logic and mechanism construction path of empowering high-quality innovative talent cultivation through the integration of science, education and industry, in response to the needs of higher education reform and industrial upgrading. Through theoretical analysis and case study methods, it systematically analyzes the prominent issues currently existing in the integration of science, education, and industry, such as insufficient system design, goal misalignment, and limited coverage, revealing its historical inevitability, theoretical rationality, and practical feasibility in three aspects. The study finds that the key to achieving deep integration is to establish a motivating mechanism for multi-party collaboration, an operational mechanism for efficient resource allocation, a scientific evaluation mechanism, and a policy guarantee mechanism. This research provides a systematic solution for the reform of innovative talent cultivation models in universities, supporting the implementation of the national strategy of revitalizing the country through science and education, and offering important guidance for promoting the deep coupling of the education chain, talent chain, and industrial chain.